Morphodynamic Model for Predicting Beach Changes Based on Bagnold's Concept and Its Applications - Uda, Takaaki; Serizawa, Masumi; Miyahara, Shiho (IntechOpen, 2018)
The authors have developed models for predicting beach changes applicable to various problems on real coasts. One of them is the contour-line-change model to predict long-term beach changes caused by the imbalance in longshore sand transport, which is a kind of N-line model. Because the calculation of the nearshore current is not needed in this model, and the computational load is small, it has an advantage in the prediction of long-term topographic changes on an extensive coast. However, the handling of boundary conditions becomes difficult when offshore coastal structures are constructed in a complicated manner, and in this regard the so-called 3D model has an advantage. Taking this point into account, the authors developed a morphodynamic model (BG model) by applying the concept of the equilibrium slope and the energetics approach, in which depth changes on 2D horizontal grids are calculated.